Perhitungan Spare Part HPSOV / PRSOV Pesawat Boeing 777 Dengan Metode Economic Order Quantity - Herbert Triyogi; Mufti Arifiin; Aprilia Sakti K (Jurnal Teknologi Kedirgantaraan, 2024)
An Indonesian airline, PT. XYZ, performs maintenance on its Boeing 777 aircraft equipped with General Electric GE90 engines at PT. GMF AeroAsia. The aircraft’s Engine Air Supply System utilizes a High Pressure Shutoff Valve (HPSOV) and a Pressure Regulating Shutoff Valve (PRSOV). Between 2019 and 2022, PT. XYZ's Boeing 777 fleet experienced 10 delays and 52 instances of HPSOV/PRSOV replacements due to valve sticking or seizing. This study aims to analyze the reliability of the HPSOV/PRSOV by calculating the Mean Time Between Failures (MTBF) and to optimize spare parts inventory management using the Economic Order Quantity (EOQ) method. The MTBF calculation yielded a value of 8,134.08 Flight Hours (FH). Additionally, the spare parts inventory analysis indicated that the most economical order quantity for each repair is 2 units, with a remaining inventory of 2 units. The total cost of the spare parts inventory is $3,033.66 USD. The findings of this study are expected to provide recommendations for PT. XYZ to improve spare parts inventory management and minimize the risk of delays in aircraft maintenance.